Dental caries experience among preschool children from anganwadi centers of Mangalore taluk: A cross-sectional study - Vijaya Hegde; Ambili Nanukuttan (Wolters Kluwer Medknow Publications, 2018)
Introduction: Anganwadi worker is the most periphery functionary of the Integrated Child Development Services scheme. They deliver services to children below the age of 6 years who form a very potential group that can be targeted for inculcating positive oral health values. Most of the anganwadi children are from rural communities who experience poverty, poor knowledge of parents, and underutilization of health services that result in poor oral as well as general health. Aim: To collect the baseline data on the dentition status of preschool children in anganwadi centers of Mangalore taluk. Methodology: The study population comprised of 530 preschool children in the age group of 3-6 years. After obtaining informed consent, dentition status was examined according to the WHO 1997 criteria. Statistical analysis was done using Statistical Package for the Social Sciences version 17. Mann-Whitney U-test was used to statistically analyze the data. The level of significance was set at P ≤ 0.05. Results: The dentition status among preschool children was poor with mean decayed, missing, filled teeth score of 2.74 ± 3.44. Gender-wise comparison did not show any statistically significant difference although girls showed a higher caries experience than boys. Conclusion: High caries experience in this study revealed that there is a great need to plan and conduct oral health promotion initiatives and treatment activities for preschool children from rural communities. Dental health services should be made available in the peripheral areas along with oral health education among parents and teachers to inculcate a positive attitude toward oral health among children.